How does Entrepreneurial Education Promote Medical Students' Entrepreneurial Orientation? - Bismala, Lila; Manurung, Yayuk Hayulina; Andriany, Dewi; Siregar, Gustina (LPPM Undiksha, 2022)
Entrepreneurial education is a carefully planned process that leads to acquiring entrepreneurial capacity and competence, equipping students with the knowledge, skills, and motivation to drive entrepreneurial success. Many goals are achieved by organizing entrepreneurial education and promoting entrepreneurial orientation. In reality, only a few students choose a career as an entrepreneur, even though they have received an entrepreneurship education. Entrepreneurship orientation is crucial because it shows innovativeness, proactiveness, and risk-taking. This study aimed to examine how entrepreneurship education promotes entrepreneurial orientation. By conducting explanatory research, the researcher intends to investigate entrepreneurship education's effect on medical students' entrepreneurial orientation. The research was conducted on medical students who took the entrepreneurial block, with the number of respondents as many as 113 students, where data collection was conducted with questionnaires. The results were obtained that entrepreneurial education can promote entrepreneurial orientation in medical students. Entrepreneurs who have an entrepreneurial orientation will be able to identify new opportunities, create tangible and intangible resources for innovation, and opportunities to launch innovative products. It must be supported by entrepreneurship education in which the quality of the application of standards, curriculum, and learning methods can promote student entrepreneurial orientation and assess entrepreneurial activities.